PROPAGAÃ‡ÃƒO VEGETATIVA E CAPACIDADE REPRODUTIVA DE ð˜”ð˜¦ð˜ð˜¢ð˜¯ð˜¤ð˜ªð˜¶ð˜® ð˜¤ð˜¢ð˜®ð˜±ð˜¦ð˜´ð˜µð˜³ð˜¦ NAUD - Cesar, O.; Marinis, G. de (REVISTA DE AGRICULTURA, 2020)
PROPAGAÃ‡ÃƒO VEGETATIVA E CAPACIDADE REPRODUTIVA DE ð˜”ð˜¦ð˜ð˜¢ð˜¯ð˜¤ð˜ªð˜¶ð˜® ð˜¤ð˜¢ð˜®ð˜±ð˜¦ð˜´ð˜µð˜³ð˜¦ NAUD